2005
DOI: 10.1002/jcb.20432
|View full text |Cite
|
Sign up to set email alerts
|

An interaction between apolipoprotein E and TERE1 with a possible association with bladder tumor formation

Abstract: TERE1, a recently discovered gene/protein appears to play a role in bladder tumor growth regulation but to date does not have clear functional correlates. The objective of this study was to gain further insight into the function of the TERE1 protein by identifying potential protein to protein interactions with TERE1 and determining whether these interactions are associated with putative growth regulatory pathways and/or bladder tumor formation. Towards this aim, we have performed a bacterial two hybrid assay a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 29 publications
2
45
1
Order By: Relevance
“…McGarvey et al [2005] have demonstrated that UBIAD1 (also known as TERE1) interacts with the carboxyl terminus of apoE. Secretion of apolipoprotein E (apoE) by brain glia has been suggested to require protein prenylation [Naidu et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McGarvey et al [2005] have demonstrated that UBIAD1 (also known as TERE1) interacts with the carboxyl terminus of apoE. Secretion of apolipoprotein E (apoE) by brain glia has been suggested to require protein prenylation [Naidu et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining protein localization will determine if mutant protein is located in the same membrane as wild-type and whether the clinical effects observed in SCCD patients are due to haploinsufficiency. Of specific interest will be examination of the published interaction between UBIAD1 and apolipoprotein E and whether SCCD mutations alter this interaction [McGarvey et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…The pcDNA3.1HisC-TERE1 plasmid and the pTRE-REV-TERE1 retrovirus plasmids were previously described (McGarvey et al, 2001(McGarvey et al, , 2003(McGarvey et al, , 2005. The mammalian CMV expression plasmids pM12-NFLAG-TERE1 and pM12-NFLAG-TBL2 were obtained from GeneCopoeia.…”
Section: Expression Vectorsmentioning
confidence: 99%
“…TERE1's role in cholesterol metabolism, suggested by the APOE interaction (McGarvey et al, 2005), was reinforced by the association of point mutations in TERE1 with SCD, a corneal cholesterol and lipid accumulation disorder (Weiss et al, 2007). We transfected HEK293 cells with Flag-tagged wild-type and SCD mutant TERE1 plasmids with point mutations at N102S, D118G, L121F, S171P, T175I, G177R, N232S, D236E, and confirmed equivalent expression levels of the wild-type, mutant, and deletion proteins (Figs.…”
Section: Tere1 Scd Mutations Alter Cholesterol Levelsmentioning
confidence: 99%
See 1 more Smart Citation